Functional Characterization of Argininosuccinate Lyase Gene Variants by Mini-Gene Splicing Assay - Wang, Yanyun; Sun, Yun; Liu, Ming; Zhang, Xiaojuan; Jiang, Tao (Frontiers in Genetics, 2019)
Objective Argininosuccinate lyase (ASL) gene mutations account for argininosuccinic aciduria (ASA). This study aimed to design a minigene construct of ASL gene in order to investigate the impact of variants on splicing. Methods The peripheral blood samples were collected from the family members, and genomic DNA was extracted for gene diagnosis using the total exon sequencing method. The novel mutation gene was cloned into pEGFP-C1 vector, and the pathogenicity of the mutation was examined in cultured cells in vitro. Results The clinical diagnosis of the proband as ASA was clear. Two pathogenic mutations, c.281G>T (p.Arg94Leu) and c.208-15 T>A were detected in the ASL gene, and the two mutations had not been reported. The minigene expression in vitro confirmed that c.208-15 T>A could cause aberrant splicing, resulting in the retention of 13 bp in intron 2 to exon 3. Conclusion Two new pathogenic mutations of ASL gene, c.208-15 T>A and c.281G>T, were found in an ASA family, which enriches the mutational profile of the ASL gene and provides a basis for genetic diagnosis of ASA. Minigenes are optimal approaches to determine whether the intron mutation can cause aberrant splicing.